2023
DOI: 10.3390/w15112120
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Practices for Hillslope Erosion Mitigation: A Case Study in Morocco

Jean Marie Vianney Nsabiyumva,
Ciro Apollonio,
Giulio Castelli
et al.

Abstract: In the last decades, the Rif area in Morocco has been frequently affected by soil erosion due to intense rainfall events. In order to help farmers improve their lives and avoid damages caused by this phenomenon, a management project (the MCA Project) aiming to grow fruit trees has been realized. The objective of this study was to evaluate, in three provinces of Morocco, the effect on the hydrological response of selected erosion control management techniques combined with olive tree plantations. The investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…They demonstrated that not only physical and chemical, but also biological properties are deeply affected by erosion. Regarding the application of agricultural practices, Vianney Nsabiyumva et al [12] evaluated, in three provinces of Morocco, their effects, combined with olive tree plantations, on the hydrological response (final infiltration, imbibition of rainwater, runoff coefficient, and soil detachment). The authors demonstrated that vegetation has an important role in moisture conservation in surficial depths in all sites and reduces runoff.…”
mentioning
confidence: 99%
“…They demonstrated that not only physical and chemical, but also biological properties are deeply affected by erosion. Regarding the application of agricultural practices, Vianney Nsabiyumva et al [12] evaluated, in three provinces of Morocco, their effects, combined with olive tree plantations, on the hydrological response (final infiltration, imbibition of rainwater, runoff coefficient, and soil detachment). The authors demonstrated that vegetation has an important role in moisture conservation in surficial depths in all sites and reduces runoff.…”
mentioning
confidence: 99%